MENINGKATKAN KESADARAN DIGITAL MARKETING PADA UMKM BERASTAGI - Yolanda, Yola; Tarigan, Purnaya Naya; Tarihoran, Anita; Pertiwi, Suci (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The purpose of this community service activity (PkM) is to increase awareness and digital marketing skills in MSMEs in Berastagi, North Sumatra. The activity was carried out as a response to the low application of digital marketing in the Berastagi UMKM environment, even though the potential for tourism and local products is very large. Limited knowledge and skills of digitalisation, lack of awareness of UMKM actors regarding digital marketing, difficulty in following the latest trends and technology and lack of utilising digital marketing are problems faced by UMKM actors in Berastagi. The objectives of community service activities have the following objectives; ah Increase UMKM awareness about the importance of digital marketing, Equip UMKM with digital marketing knowledge and skills and Improve the ability of UMKM to utilise digital marketing